Public memory of State terrorism in Argentina: management, narrative authority and disputed rights - Guglielmucci, Ana (Revista de Antropología Social, 2022)
Based on an ethnographic approach, supported by intensive field work carried out between 2009 and 2019 in Buenos Aires, this article explores the process of public institutionalization of memory of state terrorism in Argentina. On one hand, it shows how this process of inscription of memory as an object of public policies and interest has transformed the state/society relationship and the public recognition of who has the legitimacy to define the content of the institutional memory of past political violence. On the other hand, it shows how the creation of spaces of memory in former detention and torture sites has influenced new forms of articulation between human rights organizations, politicians, officials, neighbors and state workers, which have informed the relationship between narratives about past violence and demands for social and political rights in the present.